Pengaruh Metode Latihan Pliometrik Terhadap Power Tekong Pada Atlit Putri Sepak Takraw (Department of Physical Education, Sport, Health and Recreation, 2017)
The purpose of this research was to determine the effects of exercise single leg push off the leg power and leg at the club sepak takraw fulcrum in Central Java. Quantitative research methods one group pretest and posttest design, the experiments conducted on one group and 2 times the test is carried out before and after the experiment called pretest-posttest experiment called. The sample in this study were all women athletes Tekong which amounted to 7 people with a total sampling technique. Data analysis using computerized media with SSPS system version 16.0.0. The results of the study no effects of exercise single leg push off the leg power at the results sig = 0.001 and power foot fulcrum with the results sig = 0.015, in addition to measuring the results using the vertical jump explosive power with the result sig = 0.009. The conclusions of this research exercise single leg push off effect on leg power and leg at the fulcrum of the daughter of sepak takraw athlete Central Java. Suggestions in the presence of this study could be a reference for researchers who conduct similar research to further examine other factors affecting the increase in movement techniques Tekong.